COMPARISON OF VISUAL AND ANATOMICAL OUTCOMES OF EYES UNDERGOING TYPE I BOSTON KERATOPROSTHESIS WITH COMBINATION PARS PLANA VITRECTOMY WITH EYES WITHOUT COMBINATION VITRECTOMY. (September 2018) - Lim, Jennifer I.; Machen, Lindsay; Arteaga, Andrea; Karas, Faris I.; Hyde, Robert; Cao, Dingcai; Niec, Marcia; Vajaranant, Thasarat S.; Cortina, M. Soledad
Abstract : Purpose: To determine whether 1-year visual and anatomical results after surgery combining pars plana vitrectomy, Boston keratoprosthesis, and a glaucoma drainage device as needed are similar, better, or worse than Boston keratoprosthesis initial implantation alone. Methods: We performed a retrospective review of adult patients undergoing Boston keratoprosthesis at our institution. Visual acuity outcomes, anatomical results, and complication rates of patients undergoing combination surgery (including pars plana vitrectomy and a posterior glaucoma drainage device) were compared with those undergoing keratoprosthesis placement alone. Results: There were 70 eyes in the keratoprosthesis alone group and 55 eyes in the keratoprosthesis with pars plana vitrectomy group. Mean follow-up durations were 54.67 months in the keratoprosthesis alone group and 48.41 months in the combination group. Baseline mean Snellen equivalent visual acuities were worse for the combination group compared with the keratoprosthesis alone group ( P = 0.027). Visual acuities improved postoperatively by 1 month after keratoprosthesis implantation for both groups and improved three or more lines of Snellen acuity in the majority of eyes for both groups (≥72% by 12 months). Eyes undergoing pars plana vitrectomy had lower rates of de novo ( P = 0.015) and significantly lower rates of secondary procedures ( P = 0.002) at 1 year. One year complications rates for retroprosthetic membrane formation, retinal detachment, hypotony, cystoid macular edema, epiretinal membrane formation, endophthalmitis, and corneal melting were similar for both groups. Conclusion: Compared with keratoprosthesis alone, combining keratoprosthesis with pars plana vitrectomy and a glaucoma drainage device as needed, resulted in lower rates of de novo glaucoma, lower rates of additional surgical procedures, similar visual acuity outcomes at 1 year, and did not result in higher complication rates. Abstract : Combination of pars plana vitrectomy with posterior glaucoma drainage implant and Boston keratoprosthesis results in lower rates of de novo glaucoma without increased risks of complications as compared to Boston keratoprosthesis implantation alone.